Effect of rootstocks on leaf nutrients, tree growth, yield and fruit quality of Mosambi' sweet orange (Citrus sinensis) under Delhi conditions - Srivastav, Manish; Dubey, A K; Sharma, R R (The Indian Journal of Agricultural Sciences, 2005)
An investigation was carried out during 2002-2004 to assess the performance of Mosambi sweet orange [Citrus sinensis (L.) Osbeck] on 5 different rootstocks, viz 'Jambhiri', 'Karna Khatta', 'Cleopatra Mandarin', 'Soh Sarkar' and on its own roots, at main orchard of the Institute at Delhi. The elevated levels of different essential nutrients in the leaf tissue suggest the better performance of 'Kama Khatta' as rootstock in terms of vegetative growth, number of fruits/plant and juice recovery of 'Mosambi' sweet orange. The rootstock 'Cleopatra mandarin' performed well fortotal soluble solids and ascorbic acid contents. However, the acidity of juice of Mosambi fruits was minimum where Mosambi was budded on its own roots.